2017
DOI: 10.1017/aer.2017.102
|View full text |Cite
|
Sign up to set email alerts
|

A virtual engineering approach to the ship-helicopter dynamic interface – a decade of modelling and simulation research at the University of Liverpool

Abstract: This paper reviews some of the research that has been carried out at the University of Liverpool where the Flight Science and Technology Research Group has developed its Heliflight-R full-motion research simulator to create a simulation environment for the launch and recovery of maritime helicopters to ships. HELIFLIGHT-R has been used to conduct flight trials to produce simulated Ship-Helicopter Operating Limits (SHOLs). This virtual engineering approach has led to a much greater understanding of how the dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Another category of techniques involves using simulated flight data to determine wear and maintenance needs of an aircraft. For example, Owen [12] uses simulated helicopter landing data to determine the interactions between the aircraft and ship loads during takeoff and landing. Ling [13] used a Bayesian probabilistic model to analyse structural health monitoring data in conjunction with fatigue damage prognosis models.…”
Section: Related Workmentioning
confidence: 99%
“…Another category of techniques involves using simulated flight data to determine wear and maintenance needs of an aircraft. For example, Owen [12] uses simulated helicopter landing data to determine the interactions between the aircraft and ship loads during takeoff and landing. Ling [13] used a Bayesian probabilistic model to analyse structural health monitoring data in conjunction with fatigue damage prognosis models.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, landing at night reduces the visibility and availability of visual reference points and makes it extremely hard for the pilots to understand the ship's movements (Lumsden et al, 1999). In previous studies, airwake has been considered an important factor that is particularly relevant to the last phases of the landing (e.g., Hodge et al, 2012;Lumsden et al, 1999;Owen et al, 2017). In our study, pilots did not explicitly mention airwake; however, they talked about the effects of relative wind (i.e., combination of ship's movement and wind conditions), and the necessity to have information about its speed and direction.…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Creating unsteady CFD airwakes over a ship the size of the QEC, and for a significant distance downstream of the ship, where the disturbed air can still affect the aircraft, is a significant challenge. While UoL has a wealth of experience in creating CFD airwakes for smaller ships, such as Type 23/45 frigates and destroyers, and Wave Class tankers (Owen et al, 2017;Forrest and Owen, 2010), the significantly larger QEC presents a new challenge and so smallscale experiments have been conducted to compare measured data with the CFD-generated airwakes. The approach taken has been to conduct the experiments at a 1:200 scale and to apply the CFD technique at this scale to replicate the experiment.…”
Section: Qec Airwake Modellingmentioning
confidence: 99%
“…Research at UoL into ship airwakes and their integration with piloted flight simulation over the past decade or more has shown that it is essential to create airwakes using time-accurate CFD techniques, so that irregular timevarying velocity components are applied to the aircraft flight dynamics model providing a realistic experience for the pilot, in terms of handling qualities and workload (Owen et al, 2017). Delayed Detached-Eddy Simulation (DDES) lends itself well to the application of modelling the unsteady flow around bluff bodies such as ships, since DDES combines a Reynolds Averaged Navier-Stokes (RANS) approach to modelling turbulence in the near-wall boundary-layer, whilst resolving turbulent features in separated flow regions using Large-Eddy Simulation (LES) (Spalart et al, 2006); this leads to relatively modest computational requirements compared with pure LES due to relaxation of the near-wall mesh requirements.…”
Section: Qec Airwake Modellingmentioning
confidence: 99%